Evaluating the impact of agricultural projection modeling using the "IMPACT" framework - Ryan, James G. (International Food Policy Research Institute, 2003)
The International Food Policy Research Institute (IFPRI) has been engaged in food demand and supply projections since its inception in 1975. The early work was primarily focused on assembling historical data from which trends were extrapolated under varying assumptions about future influences on them. Expert opinion was used for this. In the early 1990s, IFPRI developed a global partial equilibrium trade model to base its projections on a stronger behavioral foundation. This enabled various policy scenarios to be explicitly modeled to assess their consequences on food prices, productivity, production, demand, trade, and food and nutrition security. This model was referred to as the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT). This paper attempts to assess the worth of the research that has gone into the IMPACT framework. It is the ninth in a series of studies commissioned by IFPRI to evaluate the impact of its research and related activities. It is part of a process aimed at improving the effectiveness of IFPRI’s work and documenting for donors the wisdom of investing in it. The paper will first describe the IMPACT framework, including the model and the 10 major issues it has been employed to address. This is followed by documentation of various tangible indicators of the outcomes derived from the various outputs and their influence on researchers and policymakers. This includes the extent of citations of IMPACT publications in the literature, demand for copies of the publications, media response, and derived demands for additional research. A discussion of users’ perceptions of the IMPACT information’s value and impact to users and their institutions follows. This is based upon a mail survey. A concluding section follows.